Rural Households’ Residence Status, Income Shocks, and Food Security Indicators in Conflict-Affected Nigerian States During the Covid-19 Pandemic - Oyekale, Abayomi Samuel (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
In northern Nigeria, COVID-19 exacerbated existing welfare deprivations and vulnerability already intensified by insurgencies. This study examines the effects of residence status and income shocks on food insecurity experiences (FIE) and households’ dietary diversity scores (HDDS) in northern Nigeria. The data were collected from 4,412 households in two non-longitudinal rounds (2021 and 2022) from five conflict-affected states in northern Nigeria. The data were analysed with endogenous treated Poisson regression model. The results showed slight increase in internally displaced households between 2021 and 2022. Average dietary diversity score decreased from 3.94 in 2021 to 3.28 in 2022, while food insecurity experiences slightly increased from 4.29 to 4.28. The Poisson regression showed that FIES increased (p<0.05) with income shocks, while HDDS decreased in response to the shocks. Also, being a permanent resident significantly reduced FIES (p<0.05), while internally displaced persons had higher HDDS. Education and income increased HDDS and reduced FIES. The households who received food assistance had higher FIES, and those who received seeds had higher HDDS (p<0.05). The respondents from Bauchi had significantly higher HDDS and lower FIES. It was concluded that income shocks and displacement adversely affected food security indicators. Therefore, initiatives to promote rural household resilience to income shocks through gender- and state-based livelihood support measures are essential for improving nutrition outcomes.